A companion to cultural studies - Miller, Toby 1958- (Blackwell companions in cultural studies, 2001)
This volume brings together the latest work in cultural studies, providing a synopsis of critical trends. It is designed to stimulate debate even as it acts as an introduction. It asks the question: what is cultual studies and what is not?